CFD analysis of cross-ventilation of a generic isolated building with asymmetric opening positions: Impact of roof angle and opening location. (February 2015) - Perén, J.I.; van Hooff, T.; Leite, B.C.C.; Blocken, B.
Abstract: The position of window openings and roof inclination are important parameters determining the effectiveness of wind-driven cross-ventilation in buildings. Many studies on natural ventilation have been performed in the past, however, a detailed review of the literature indicates that the majority of these studies focused on flat roofs with symmetric opening positions. There is a lack of research that analyzes the impact of asymmetric opening positions and roof inclination on natural ventilation potential. This paper presents Computational Fluid Dynamics (CFD) simulations to analyze the natural ventilation flow in a generic isolated building with different vertical positions of the outlet opening – yielding asymmetric opening positions – and five different roof inclination angles. The simulations are performed using the 3D steady Reynolds-Averaged Navier–Stokes (RANS) equations. They are based on a grid-sensitivity analysis and on validation with previously published wind-tunnel measurements using Particle Image Velocimetry. The results show that the shear-stress transport (SST) k-ω and the Renormalization-group (RNG) k-ε turbulence models provide the best agreement with the experimental data. It is also shown that the roof inclination angle has a significant effect on the ventilation flow; the volume flow rate increases by more than 22%. The maximum local indoor air velocity increases considerably when the inclination angle is increased, however, the differences in the average velocity in the occupied zone are only around 7%. The vertical position of the outlet opening has a relatively small impact on the volume flow rate (less than 4%), and a small influence on the average velocity in the occupied zone (<5%). Graphical abstract: Highlights: CFD simulations of cross ventilation with 3D steady RANS and various turbulence models. Influence of roof inclination angle and outlet opening position. Grid-sensitivity analysis and validation with PIV measurements. SST k-ω model and RNG k-ε model show best performance. Roof inclination angle has much larger effect than position of outlet opening.